Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 1999
DOI: 10.1115/99-gt-101
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Deterministic Correlations for a Turbine Stage: Part 2 — Unsteady Flow Analysis

Abstract: The first part of this paper analysed the time-averaged flow in a transonic single stage turbine. In this second part, we analyse the three-dimensional unsteady flow and temporal correlations in the rotor frame of reference. Two main conclusions are deduced from the comparison of each correlation. First, all correlations have the same order of magnitude. This is an important conclusion for models that handle the interaction between blade rows, because the temporal correlations are usually neglected. Second, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…However, it has recently been demonstrated that purely spatial correlations are weaker than purely temporal ones for a transonic single-stage turbine [6,7]. The aim of this paper is to con rm this observation through an estimation of their in uence.…”
Section: …5 †mentioning
confidence: 83%
See 1 more Smart Citation
“…However, it has recently been demonstrated that purely spatial correlations are weaker than purely temporal ones for a transonic single-stage turbine [6,7]. The aim of this paper is to con rm this observation through an estimation of their in uence.…”
Section: …5 †mentioning
confidence: 83%
“…The test case is the transonic turbine stage VEGA2. Because the unsteadinesses of the stage occur mainly in the rotor domain [6,7], the impact of the deterministic correlations is only studied on this blade row.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The simulations were run without tip clearance and with an algebraic turbulence model. A complete analysis of the simulations is available in [7], [8]. The main particularity of this testcase is recalled hereafter.…”
Section: Transonic Turbine Stagementioning
confidence: 99%
“…Bardoux et al [7,8] showed that including the deterministic stresses in the 3-D simulation of the VEGA2 rotor allows to capture the mean effect of the unsteadiness on the mean steady flow. They also showed that the purely temporal part of the deterministic stresses cannot be neglected, contrary to the assumptions of the closure proposed by Adamczyk [3].…”
Section: Relative Importance Of the Deterministic And Circumferentialmentioning
confidence: 99%
See 1 more Smart Citation